Atypical mycobacterial keratitis: Clinical outcome in nonrefractive surgery cases - Kshyanaprava Priyadarshini; Smruti Rekha Priyadarshini; Srikant Kumar Sahu; Himansu Sekhar Behera; Sujata Das (Indian Journal of Ophthalmology)
Purpose: To identify the predisposing factors, clinico-microbiological profiles, and treatment responses in patients with atypical mycobacterial keratitis. Methods: The study retrospectively analyzed patients who presented at a tertiary eyecare center in eastern India with atypical mycobacterial keratitis between 2008 and 2021. The diagnostic criteria included cases positive for acid-fast bacilli on Ziehl–Nielsen stain or culture. The antibiotic susceptibility pattern was observed, and treatment was initiated accordingly. Results: Out of the 29 cases, ocular predisposing factors were present in 62.1% with an antecedent history of trauma, and vegetative matter was the most common risk factor. There was no predisposing association with systemic conditions in any case. A long lag time was observed between the onset of corneal infection and presentation in 79.3% of cases, with the average time being 43.7 days. Clinical signs mimicked fungal keratitis in most cases. Typical cracked windshield appearance was only observed in two cases. Two patients presented with clinical pictures like peripheral ulcerative keratitis. Topical amikacin was used as treatment in 28 cases. Based on disk diffusion assay, 28 (96.5%) isolates were sensitive to amikacin. Twelve (41.3%) were sensitive to vancomycin, six (20.6%) to gatifloxacin, six (20.6%) to ciprofloxacin, and four (13.7%) to moxifloxacin. Twelve participants showed good final visual acuity posttreatment, which improved to over two lines of Snellen’s visual acuity chart (44.5%). Conclusion: Atypical mycobacteria keratitis may not present with classically described clinical features. The duration of presentation, clinical presentation, special microbiological stains, targeted therapy, and antibiotic susceptibility patterns are the key to successfully managing these intractable infections and obtaining favorable outcomes.